Staying on the Top: A Case Study of Johnson&Johnson - Mikhail Salazkin (Foresight and STI Governance)
Favourite of contemporary economic model is the area with an unusual name - Peripherals. In terms of the renowned McKinsey’s experts, «periphery» means the new, emerging markets or newly established companies in any sector. It is the periphery where the latest technology and products with breakthrough potential emerge. Consequently, the periphery of the business sector is a hidden horizon, which can be identified only by the means of Foresight. Johnson & Johnson regularly implements corporate Foresight. The company therefore succeeds to stay ahead of the curve for a long time and dominate the global market.